INDONESIA MERUPAKAN NEGARA DAN MASYARAKAT MULTIKULTURAL, BUKAN MAJEMUK - Ola Rongan Wilhelmus (Lembaga Penelitian STKIP Widya Yuwana, 2026)
Many discussions and scholarly literature frequently have some difficulties to distinguish the meaning of the terms